2019
DOI: 10.1002/jcp.29136
|View full text |Cite
|
Sign up to set email alerts
|

PIWI‐interacting RNA 39980 promotes tumor progression and reduces drug sensitivity in neuroblastoma cells

Abstract: Neuroblastoma (NB) is the leading pediatric cancer known for its heterogeneity and clinical aggressiveness leading to chemoresistance. Recent evidence in small RNA research has led to the discovery of PIWI-interacting RNAs (piRNAs) which work in an orchestrated fashion to modulate gene expression both in homeostatic conditions and abnormalities like cancer including NB. This study aims to decipher the possible role of a repeat-derived piRNA, piR-39980 (identified from our previous piRNA profiling study in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…Neither piR‐FTH1 nor piR‐932 was present in our samples. A few other studies have also reported functional mechanisms of piRNAs in cancer but they lack validation of the interaction with PIWI‐proteins and two of the reported piRNAs align with snoRNAs 47‐51 . Although these findings shed light on the possible functional roles of individual piRNAs in cancer, whether and how the majority of the observed dysregulated piRNAs in cancer affect tumorigenesis remain unknown.…”
Section: Discussionmentioning
confidence: 90%
“…Neither piR‐FTH1 nor piR‐932 was present in our samples. A few other studies have also reported functional mechanisms of piRNAs in cancer but they lack validation of the interaction with PIWI‐proteins and two of the reported piRNAs align with snoRNAs 47‐51 . Although these findings shed light on the possible functional roles of individual piRNAs in cancer, whether and how the majority of the observed dysregulated piRNAs in cancer affect tumorigenesis remain unknown.…”
Section: Discussionmentioning
confidence: 90%
“…OS cells were seeded at a density of 2 × 10 5 cells/well and transfected with 80 nM mimic/scramble/inhibitor/NC. After 24 h of transfection, nuclear accumulation of phosphorylated histone H2AX (γ‐H2AX) in OS cells was detected by performing immunofluorescence microscopy of γ‐H2AX as reported in our previous study [Roy et al., ]. Rabbit anti‐γ‐H2AX (phosphor S139) antibody (ab81299, Abcam) and DyLight‐488 conjugated secondary antibody (ab96899, Abcam) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability and proliferation were measured by MTT {3‐(4,5‐dimethylthiazol‐2yl)−2,5‐diphenyltetrazolium bromide} reduction assay according to our previous method . Briefly, 5 × 10 3 HT1080 cells per 100 μL of culture media were seeded in triplicate in a 96‐well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability and proliferation were measured by MTT {3-(4,5-dimethylthiazol-2yl)−2,5-diphenyltetrazolium bro-mide} reduction assay according to our previous method. 24 Briefly, 5 × 10 3 HT1080 cells per 100 μL of culture media were seeded in triplicate in a 96-well plate. When cells reach confluency, they were transfected with miR-197-3p mimic and scramble in a concentration-dependent manner (20,40,60,80, and 100 nM).…”
Section: Cell Viability Assaymentioning
confidence: 99%